Spatial Characteristics of Mithila Architecture - Pokhrel, Aanchal; Manandhar Joshi, Shailita (KEC Journal of Science and Engineering, 2024)
Mithila, a region steeped in history and culture, nestled within the Indian subcontinent, emerges as a captivating tapestry of geographical and architectural heritage. Bounded by significant natural landmarks, Mithila's rich history dates back to 6000 BCE, enduring diverse epochs under various rulers. In the face of relentless urbanization, the study of Mithila's architecture becomes a crucial endeavor to conserve the essence of this community. This research explores the intricate layers of Mithila's architectural legacy, delving into the living history of its people and providing a roadmap for integrating tradition into contemporary developments. Through a comprehensive literature review, the study navigates cultural and historical transitions, architectural intricacies, and traditional residential structures in Mithila. The research methodology employs qualitative methods, including participant observation and semi-structured interviews, focusing on Janakpur as a research site. Analyzing spatial characteristics reveals intentional orientations, meticulous planning, and the ingenious use of bamboo, mud plaster, and vibrant paintings in building materials and technology. The elevation treatment of Mithila houses emerges as a dynamic manifestation of cultural identity seamlessly blended with architectural innovation. This research contributes to the discourse on cultural and heritage conservation, emphasizing the urgency of empowering local communities to preserve and celebrate Mithila's unique architectural legacy.